Porphyrin and photodynamic therapy as tools against Acinetobacter baumannii - Isabela Dadda dos Reis; Marcelle Oliveira Garcia; Suelen Lopes Lussanrriaga; Kamila Furtado da Cunha; Bernardo Almeida Iglesias; Daniela Fernandes Ramos (Antonie van Leeuwenhoek, 2026)
Abstract Since the 1990s, Acinetobacter baumannii has become a major global concern owing to its high incidence in hospital-acquired infections. Although antimicrobial resistance is a natural process, it has been enhanced by the widespread use of antimicrobials in human and animal healthcare and is considered a global priority in the development of new drugs. Therefore, antibacterial photodynamic therapy has gained prominence for treating infections caused by multidrug-resistant microorganisms. This involves the use of photosensitizers, which, in the presence of light radiation at the appropriate wavelength, form reactive oxygen species, causing oxidative damage to bacterial cells. This review aims to critically evaluate the available literature on the efficacy of antimicrobial photodynamic therapy using porphyrins as photosensitizers against strains of A. baumannii . A search was conducted in five databases using the following keywords: “ Acinetobacter baumannii ,” “photoinactivation,” and “porphyrin.” Eight articles from different periods were selected, evaluating in vitro and in vivo assays at different concentrations and light incidence. Different concentrations of porphyrins interact differently with wavelengths, resulting in variable photosensitizer behavior, indicating that activity is also linked to virulence mechanisms, such as biofilm formation. Regarding multidrug-resistant strains, no relationship was observed between activity and resistance; however, higher concentrations of the compound were required in minimum inhibitory concentration assays. The compiled data provide important insights into the potential of porphyrins as alternatives to available antimicrobials and evaluate different parameters that influence their activity.